Normative reference of standing long jump for colombian schoolchildren aged 9-17.9 years: The fuprecol study (2017)
The purpose of this study was to generate normative values for the standing long jump (SLJ) test in 9- to 17.9-year olds and to investigate sex and age-group differences. The sample comprised 8,034 healthy Colombian schoolchildren [boys n = 3,488 and girls n = 4,546; mean (SD) age 12.8 (±2.3) years old]. Each participant performed two SLJ. Centile smoothed curves, percentile, and tables for the third, 10th, 25th, 50th, 75th, 90th, and 97th percentiles were calculated using Cole's Lambda-Mu-Sigma method. The 2-way analysis of variance tests and Cohen's d showed that the maximum SLJ (centimeter) was higher in boys than in girls across age groups (p less than 0.01), reaching the peak at 13 years. Posthoc analyses within the sexes showed yearly increases in SLJ in all ages. In boys, the 50th percentile SLJ score ranged from 109 to 165 cm. In girls, the 50th percentile jump ranged from 96 to 120 cm. For girls, jump scores increased yearly from age 9 to 12.9 years before reaching a plateau at an age between 13 and 15.9. Our results provide, for the first time, sex- and age-specific SLJ reference values for Colombian schoolchildren aged 9-17.9 years. The normative values presented in this study provide the basis for the determination of the proposed age- and sex-specific standards for the FUPRECOL (Association for Muscular Strength with Early Manifestation of Cardiovascular Disease Risk Factors Among Colombian Children and Adolescents) Study-Physical fitness battery for children and adolescents. © 2016 National Strength and Conditioning Association.